THE RELATIONSHIP BETWEEN BALANCED ORGANIZATIONAL VALUES AND ORGANIZATIONAL EFFECTIVENESS: EVIDENCE FROM BUSINESS PRACTICE - Malbašić, Ivan (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Organizational values are a part of the core ideology of any organization; therefore, managing organizational values is one of the preconditions for achieving business success. However, the question arises of how to manage organizational values to increase overall business success. The main research question asked in this paper is whether organizations with balanced values, i.e., those with an equal representation of values from different categories with a common focus, are more effective than those with imbalanced values. To test the research question, a study of 24 Croatian companies was conducted. The level of balanced values was measured with the Mission-based model of organizational values, distinguishing between four basic value categories—business values, relational values, development values, and contribution values. In addition to researching the impact of balanced organizational values on the overall level of organizational effectiveness, the impact of that balance was also investigated for the five different perspectives of organizational effectiveness based on the Balanced Scorecard approach. The findings indicate that organizations with balanced organizational values are, in general, more effective than organizations with imbalanced values. This paper therefore contributes to a better understanding of the role of organizational values in modern business and particularly to an understanding of the importance and role of balanced organizational values.